Evaluation of Combustion Processes for Production of Feedstock Chemicals from Ammonium Sulfate and Ammonium Bisulfate - Y. Liske; S. Kapila; V. Flanigan; P. Nam; S. Lorbert (Journal of Hazardous Substance Research, 1999)
The combustion of ammonium bisulfate and ammonium sulfate solutions in hydrocarbon/air flames was studied under varied flame conditions. The objective of the study was to optimize the recovery of sulfur value from aqueous waste streams containing these salts. Combustion of ammonium sulfates yielded different sulfur species such as sulfur dioxide (SO2 ), hydrogen sulfide (H2S), and carbonyl sulfide (COS). The types of sulfur species obtained and their yields were dependent on the flame stoichiometry. When combustion was carried out in stochiometric flames or in flames with excess oxygen, the sulfur present in the salts was quantitatively converted to SO2 . However, these flames also produced nitrogen oxides (NOx ) above the 200ppm level. Combustion of ammonium sulfates in the sub-stoichiometric (oxygen-deficient) flames resulted in the formation of reduced sulfur species, particularly H2S. This species accounted for nearly 90% of the total sulfur present in the salts. Introduction of a secondary air stream in cooler regions of the combustor led to quantitative oxidation of H2 S and other reduced species such as COS to SO2. The SO2 obtained through the secondary oxidation contained nitrogen oxides at comparably lower levels.
Keywords: combustion; ammonium sulfate; ammonium bisulfate; sulfur species